Carbon cycle model simulations using BICYCLE-SE over the last 5 millions years with focus on the 405-kyr periodicities in 13C - Peter Köhler (PANGAEA, 2025)
Using the carbon cycle model BICYCLE-SE I simulated carbon cycle changes that tried to agree with marine δ13C reconstructions. In doing so the model is in some scenarios prescribed with δ13C data, or nudged to δ13C data. Necessary corrections in the model-internal 13C cycle can in post-processing be used to evaluate if the δ13C signature of geological carbon sources (volcanic CO2 or carbonate rock weathering) external to the model might be responsible for the necessary changes that align the model with the data. The data are obtained from 9 simulation scenarios, which are between 210 kyr and 5 Myr long.